O ensino de Língua Portuguesa em Moçambique no período colonial de 1940 a 1960: Uma visão historiográfica - Arakaki, Nancy Aparecida (2007)
This Dissertation presents as main theme the teaching of Portuguese in Mozambique during the colonial period of 1940 to 1960, under a historiographical view. In order to make a reflection about the means and the pedagogical models which the Portuguese ideological state took advantage of, it seemed relevant to focus on the teaching of the Catholic and Protestant missions destined to the Mozambique people. The historical and educational scene necessary to this study is centralized on a Lusitanian perspective limited to Portugal and Mozambique. Both Continental Portugal nationalized and civilized action under the responsibility of the missions were focused on the engagement of diffusion and implantation of the Portuguese language along with evangelization. The teaching in Mozambique was designed to serve the trans(formation) of the bantu man, aiming the birth of a new Lusitanian and Mozambique s identity. The cultural adaptation process sustained by the teaching of the Portuguese language is strongly pointed by a pedagogical model which generates racial and social segregation, because it was as well based on a dichotomously and strictly eurocentric educational system. Based on the theoretical reference of the Historiographical Linguistics and having as its corpus the Junta de Investigações do Ultramar monograph treatise, called Protestantismo em África (1960), written by José Júlio Gonçalves, the purpose of this Dissertion is to present a distinction between the teaching ministered by the Catholic Church and the one ministered by the Protestant Churches. Protestantismo em África brings a worthy scientific contribution which allows the teaching of the Portuguese language at the colonial period in Mozambique to be reviewed in a way to identify and establish the differences and similarities between the Catholic and the Protestant missionary works. The review is possible taking on account the textbooks adopted for alphabetization in Portuguese language which were produced specially by each of the involved missions. The textbooks from the colonial period present a Portuguese pedagogical thought enough to promote the moral and social values idealized by the dominant classes and conceived by the dominated classes, that, altogether, make flourish through the African territory a new Lusitanian and Mozambique s vision society.